Inflammatory Effects of High and Moderate Intensity Exercise—A Systematic Review - Cerqueira, Érica; Marinho, Daniel A.; Neiva, Henrique P.; Lourenço, Olga (Frontiers in Physiology, 2020)
Background: Exercise leads to a robust inflammatory response mainly characterized by the mobilization of leukocytes and an increase in circulating inflammatory mediators produced by immune cells and directly from the active muscle tissue. Both positive and negative effects on immune function and susceptibility to minor illness have been observed following different training protocols. While engaging in moderate activity may enhance immune function above sedentary levels, excessive amounts of prolonged, high-intensity exercise may impair immune function. Thus, the aim of the present review was to clarify the inflammatory effects in response to different exercise intensities. Methods: Search was performed on PubMed and was completed on July 31st, 2017. The studies were eligible if they met the predefined inclusion criteria: a) observational or interventional studies, b) conducted in healthy adults (18-65 years), c) written in Portuguese, English or Spanish, d) including moderate and/or intense exercise. Eighteen articles were included. The specific components that were examined included circulating blood levels of cytokines, leukocytes, creatine kinase (CK) and C-reactive protein (CRP). The methodological quality of the included studies was assessed. Results: Most of the intervention studies showed changes in the assessed biomarkers, although these changes were not consistent. White blood cells (WBC) had an increase immediately after intensive exercise (> 64 % VO2max), without alteration after moderate exercise (46 - 64% VO2max). The results suggested an elevation of the pro-inflammatory cytokines, namely IL-6, followed by an elevation of IL-10 that were more evident after intensive exercise bouts. CRP increased both after intense and moderate exercise, with peak increases up to 28h. CK increased only after intensive and long exercising. Conclusion: In summary, intense long exercise can lead, in general, to higher levels of inflammatory mediators, and thus might increase the risk of injury and chronic inflammation. In contrast, moderate exercise or vigorous exercise with appropriate resting periods can achieve maximum benefit.